Unpredictability of SARS-CoV-2: Pneumoperitoneum a rare complication - Rehman, Hassan Ur; Javed, Ayesha; Akhunzada, Hawwa Ahmad; Tariq, Nabeel; Abbassi, Nida (Journal of the Pakistan Medical Association, 2022)
COVID-19 is a viral disease caused by a novel coronavirus that ignited the ongoing pandemic in December 2019. The infected patients may be asymptomatic, have fever and myalgias, develop mild pulmonary symptoms or go into overt respiratory failure. There is also a significant number of patients with gastrointestinal and thromboembolic disease presentation and complications. Since respiratory features predominate, physicians might miss other systemic manifestations. Here, we present the case of a 62-year-old male who was admitted with COVID-19 pneumonia and later went into septic shock and then developed acute abdomen caused by small gut perforation. Keywords: COVID-19, Tocilizumab, gastrointestinal perforation (GI perforation), deep vein thrombosis.